Students’ interest and self-efficacy and the impact of changing learning environments - Schweder, Sabine; Raufelder, Diana (Contemporary educational psychology, 2022)
•Large dataset (754) on instruction expanded via self-directed learning (SDL).•Instruction and SDL together promote interest and self-efficacy.•Instruction is an essential precondition for the growth of the variables.•Insight regarding the ways in which interest and self-efficacy work together.•Interest and self-efficacy influence each other in a short-and long-term way. Interest and self-efficacy are two key components of motivation and learning, both of which decrease during adolescence. The situated expectancy-value theory (SEVT), recently formulated by Eccles and Wigfield (2020), provides a detailed perspective on critical components of learning situations and the ways in which competence beliefs (e.g., self-efficacy) and value perceptions (e.g., interest) work together to impact students’ achievement. This four-wave study includes data from 754 German secondary school students (MAge = 13.56; SD = 1.2; 49.4% girls). The study analysis employed two latent change models and a latent neighbor change model with covariates (sex, age, grades) to examine the development and interconnections between interest and self-efficacy. The schools included in the sample expand instruction via two self-directed learning intervals during the school year. During the self-directed learning intervals, learning was driven by the students’ preferences for subject matter rather than curricular objectives. The findings indicate that students’ interest and self-efficacy increased not only during self-directed learning but also over the course of the school year. The results suggest that an instructional environment that has been enriched by SDL intervals benefits the interplay between interest and self-efficacy.